On-farm conservation of traditional mango varieties by custodian farmers in Uttar Pradesh - Shailendra Rajan
Farmers in Uttar Pradesh play a crucial role as guardians of the state's diverse mango heritage, actively contributing to the evolution and on-farm conservation of numerous varieties. This extensive study across 23 key mango-growing districts in Uttar Pradesh sought to identify custodian farmers employing Indigenous Technical Knowledge (ITK) to conserve a minimum of ten mango varieties within their orchards. District-wise analysis unveiled a concentration of custodian farmers, with Lucknow district standing out at 31.68%, showcasing their dedication to maintaining the highest number of traditional varieties. Across districts, substantial variations were noted in fruit maturity, suitability, color (peel and pulp), size, quality, and fiber content. Saharanpur district emerged as a notable area where custodian farmers dedicated significant orchard space to mango cultivation. The discovery of a 250-year-old orchard in Bulandshahr district adds a historical dimension to the custodian farmers' commitment. Malihabad nurseries in Lucknow took center stage as primary sources for planting materials of traditional varieties, highlighting their pivotal role in supporting on-farm conservation efforts. This emphasizes the synergy between custodian farmers and local nurseries, both rooted in ITK practices. The study identified astrong correlation (r=0.997), emphasizing that the number of traditional varieties significantly contributes to on-farm conservation, underscoring the importance of preserving mango diversity. This research illuminates the proactive measures taken by Uttar Pradesh farmers, providing insights with potential implications for sustainable agriculture and biodiversity conservation